2016
DOI: 10.22194/jgiass/4.4.761
|View full text |Cite
|
Sign up to set email alerts
|

Palatability of Subterranean Clover and Some Perennial Grasses and Legume Forage Crops

Abstract: In vivo trials using the method of "trough cafeteria" the palatability or the preference of sheep (Pleven Blackface sheep) to the subterranean clover and to other commonly used perennial forage crops was studied. The observations were done on pure swards of subterranean clover (Trifolium subterraneum ssp. brachycalicinum) (cv."Antas"), birdsfoot trefoil (Lotus corniculatus L.) (cv. "Targovishte 1"), sainfoin (Onobrychis viciaefolia L.) (local population), cocksfoot (Dactylis glomerata L.) (cv. "Dabrava") and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Wobeto et al [19] reported that crude protein content on Manihot esculenta leaves reach 23.3 -35.9% while Ipomea batatas reach 14.9% [20] until 24.9% [21]. Sheep has a preference and an instinct to choose forage with better taste or nutritional value that is expressed as palatability value [22].…”
Section: Forage Diversitymentioning
confidence: 99%
“…Wobeto et al [19] reported that crude protein content on Manihot esculenta leaves reach 23.3 -35.9% while Ipomea batatas reach 14.9% [20] until 24.9% [21]. Sheep has a preference and an instinct to choose forage with better taste or nutritional value that is expressed as palatability value [22].…”
Section: Forage Diversitymentioning
confidence: 99%